Characterization of a self-calibrating, high-precision, stacked-stage, vertical dual-axis goniometer - Mendenhall, Marcus H. (Metrologia, 2016)
We present details on the alignment and calibration of a goniometer assembly consisting two stacked, optically encoded, vertical axis rotation stages. A technique for its calibration is presented that utilizes a stable, uncalibrated, third stage to position a mirror in conjunction with a nulling autocollimator. Such a system provides a self-calibrating set of angular stages with absolute accuracy of ±0.1 second of plane angle (k=2 expanded uncertainty) around the full circle, suitable for laboratory application. This calibration technique permits in situ, absolute angular calibration of an operational goniometer assembly that is requisite for fully traceable angle measurement, as the installation of the encoder is known to change its performance from the angular calibration data provided by the manufacturer.